Cat vs. cat : keeping peace when you have more than one cat - Johnson-Bennett, Pam, 1954- (Penguin Books, 2004)
A guide for cat owners that discusses how to prepare and maintain a household for multiple cats, and covers relationships and hierarchies, bad behavior patterns, and other related topics.